COMPARISON OF BOUNCE CHARACTERISTICS ON THREE TYPES OF TRAMPOLINES - William A. Sands; Madison K. Varmette; Gregory C. Bogdanis; Olyvia Donti; Bryce V. Murphy; Troy J. Taylor (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
Trampoline use has skyrocketed in recent years in a variety of recreational contexts and among athletes in sports ranging from gymnastics and diving to skiing and snowboarding. The purpose of this study was to examine the bounce characteristics elicited by athletes bouncing on three types of trampolines. Tumbl Trak, Standard, and Super Tramp trampolines were assessed by 10 experienced trampoline and acrobatic athletes (5 males, 5 females). A triaxial accelerometer (250 Hz) characterized the 10 highest controlled bounces on each trampoline and each athlete. Repeated measures ANOVAs showed statistical differences in bounce characteristics: time from bounce start to peak acceleration (p<.001, ƞ2 =0.82), time from peak acceleration to bounce end (p=.030, ƞ2 =0.40), and total bounce time (p<0.001, ƞ2 =0.78, jump height (p<.001, ƞ2 =0.95) peak acceleration (p=.015, ƞ2 =0.37), and flight time (p<.001, ƞ2 =0.97).  Average acceleration, force, and allometrically scaled average force were not statistically different (p˃.140, ƞ2=0.20). The stiffest trampoline with the least time values, peak accelerations, and jump heights was the Tumbl Trak, followed by the Standard trampoline, and Super Tramp, respectively. This information may help practitioners and others to understand the bounce behaviors of athletes on these types of trampolines.